A Case of Pneumothorax due to High-Flow Nasal Cannula Oxygen Therapy - Çapan Konca; Hasan Öğünç Apaydın; Mehmet Geyik (Galenos Yayinevi, 2017)
Invasive and noninvasive mechanical ventilation (MV) applications are used for patients with respiratory insufficiency. Noninvasive MV has been increasingly used in pediatric intensive care units in recent years. For this purpose, high-flow nasal cannula (HFNC) oxygen therapy is a treatment method that has been increasingly used. Despite the numerous studies reporting the advantages of this method, there are also a few studies reporting that undesirable conditions can be observed. In this paper, in order to contribute to the literature, we present a 3-month-old baby who developed pneumothorax during HFNC implementation.